Model Pembelajaran Kreatif Produktif untuk Meningkatkan Hasil Belajar Siswa Pada Materi Menulis Puisi Bebas di MTs Negeri 3 Kebumen Tahun Pelajaran 2022/2023 - Siti Nurhaida (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2023)
This study aims to improve the learning outcomes of free poetry writing through the application of a Creative Productive Learning Model and assist teachers in evaluating various student and teacher weaknesses in the learning outcomes achieved as a result of the previous teaching and learning process. This research contains efforts to overcome students' problems in learning Indonesian in writing free poetry in class VII-H of MTs Negeri 3 Kebumen in the 2022/2023 academic year. The problem that occurred in this class was that the learning outcomes of free poetry writing were still low. There are 34 students in class VIII-H, consisting of 22 male students and 12 female students. The average score is still 74.91 with a classical completeness of 58.82%. Students still have difficulties in writing free poetry, especially those related to the suitability of content with themes, rhymes, diction, and the use of figure of speech. After the application of the Creative Productive Learning Model there has been an increase in learning outcomes or at the second meeting which can be observed based on predetermined indicators. Evidence of increased learning outcomes in writing free poetry in class VIII-H students of MTs Negeri 3 Kebumen through the Creative Productive Learning Model is shown by the percentage of student learning outcomes that has increased, from before the application of the Creative Productive Learning Model 58.82%, to 94.12% after application of Productive Creative Learning Model. While the average value of learning outcomes also increased from before the implementation of the Productive Creative Learning Model 74.91, to 84.36.